Buckling and postbuckling of carbon nanotube-reinforced composite cylindrical panels subjected to axial compression in thermal environments - Trang, Le Thi Nhu; Tung, Hoang Van (Vietnam Journal of Mechanics, 2018)
This paper presents an analytical investigation on the buckling and postbuckling behavior of thin composite cylindrical panels reinforced by single walled carbon nanotubes (SWCNTs), exposed to thermal environments and subjected to uniform axial compression. Material properties of isotropic matrix phase and carbon nanotubes are assumed to be temperature dependent, and effective properties of carbon nanotube-reinforced composite (CNTRC) are functionally graded in the thickness direction and estimated by extended rule of mixture. Governing equations are based on the classical thin shell theory taking von Karman-Donnell nonlinearity and initial geometrical imperfection into consideration. Approximate solutions are assumed to satisfy simply supported boundary conditions and Galerkin procedure is applied to derive explicit expressions of buckling loads and load-deflection relation. Effects of volume fraction and distribution type of carbon nanotubes, geometrical parameters, elevated temperature and initial imperfection on the nonlinear stability of CNTRC cylindrical panels are analyzed and discussed. The novelty of the present study is that closed-form results of buckling load and nonlinear load-deflection relation can be readily used to analyze the buckling and postbuckling behaviors of axially loaded CNTRC cylindrical panels.